2021
DOI: 10.1037/rep0000333
|View full text |Cite
|
Sign up to set email alerts
|

Pain interference and quality of life in combat veterans: Examining the roles of posttraumatic stress disorder, traumatic brain injury, and sleep quality.

Abstract: Objective: The goal of this study was to examine the associations among posttraumatic stress disorder (PTSD), traumatic brain injury (TBI), sleep quality, pain interference, and quality of life in combat veterans. Method: Veterans (N ϭ 289, 86.51% male) completed the Mid-Atlantic MIRECC Assessment of Traumatic Brain Injury, the Clinician-Administered PTSD Scale for DSM-5, and measures of sleep quality, pain interference, and quality of life. Results: Hierarchical linear regressions evaluated associations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Because ADSMs are always screened for mTBI as well as these symptoms before and after any deployment, we are confident that the symptoms are a sequalae of mTBI and not pre-existing conditions. Further, these findings are consistent with other studies that have investigated the association between TBI and other employment-related outcomes [14,29,33,[39][40][41][42][43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 91%
“…Because ADSMs are always screened for mTBI as well as these symptoms before and after any deployment, we are confident that the symptoms are a sequalae of mTBI and not pre-existing conditions. Further, these findings are consistent with other studies that have investigated the association between TBI and other employment-related outcomes [14,29,33,[39][40][41][42][43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 91%
“…The investigators concluded that sleep-focused treatments may be an effective way to facilitate psychiatric recovery (Rusch et al, 2015). Similarly, Ord et al (2021) demonstrated that sleep was significantly associated with quality of life beyond symptoms of PTSD and deployment TBI history in post-9/11 veterans and suggested that behavioral sleep treatments may be beneficial as an adjunct or first-line treatment for veterans with PTSD and/or TBI history. Taken as a whole, results of the present study and extant research underscore the importance of comprehensive rehabilitation approaches when treating individuals with PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of application to PCAFC, over 60% of applicants had a musculoskeletal disorder and nearly half had a pain code of some type (Van Houtven, Smith, Stechuchak, et al, 2019). It is vital to identify and treat pain for these Veterans due to the quality of life reductions that arise for those experiencing chronic pain and the associated debilitating comorbidities that commonly occur with chronic pain, including depression and substance use (Kerns & Dobscha, 2009; Murphy et al, 2022; Naylor et al, 2019; Ord et al, 2021; Saconi et al, 2023). To date, we know surprisingly little about how services and supports to family caregivers affect care recipient health and well-being (Coe et al, 2021).…”
Section: Introductionmentioning
confidence: 99%